The historian beneath the skin: Embodiment as methodology in colonial India - Topdar, Sudipa (History compass, 2019)
While the pioneering historians of medicine and sexuality in colonial India have left us a rich scholarly legacy, this article contributes to the history of the body by examining recent historiographical trends outside these realms. I provoke and ask: in what other imaginative ways can we understand our body, its meanings, and its engagement with culture and self. I use embodiment as an analytical category and pedagogical device that offers promising possibilities to access wider social, economic, and epistemological shifts in history. When intersected with other critical concepts such as gender, race, nation, class, caste, and sexuality, embodiment becomes a bridge to the past for understanding how key moments were experienced and lived. Embodiment provides a point of convergence at which both the discursive body and its experiences are given equal attention in order to understand histories. I begin this article with an overview of foundational moments in the historiography of embodiment as a category of historical analysis. Subsequently, I explore three main axes of historiographical pursuits keeping embodiment as the pivot: first, social inscriptions on the body; second, the performance of gender; and third, embodiment as experience.